Evaluation of cholinesterase level in workers exposed to organophosphates - A Barkhordri; T Raee Bandpey; SH Hekmati Moghaddam; MH Mosadegh; H Fallahzadeh (طب کار)
Background: Organophosphates use in agriculture and concern about their effects on human is increasing. This study was conducted to investigate the activity of blood cholinesterase in sprayers. Methods: In a descriptive and analytical cross-sectional study, 60 (30 sprayers and 30 control individuals) with age range of 29-62 years, mean age of 44.33±8.55 years were studied and the results were analyzed using SPSS version 11. Results: The average and standard deviation of erythrocyte cholinesterase (AchE) and plasma cholinesterase (PchE) concentration was 5573.2± 1229.51 U/L and 144.73±52.3 IU/grHgb, respectively. Minimum and Maximum activity of erythrocyte cholinesterase was also 71.07 and 291.9 IU /gr, respectively. The average concentration of both erythrocyte cholinesterase (AchE) and plasma cholinesterase (PchE) in the case group was lower than the control group. A significant difference was observed between two groups (p<0.05). Conclusion: In conclusion, high exposure to organophosphates was observed and it is needed to implement the occupational health program for prevention of health effects.